Temporal dynamics of early inflammatory markers after professional dental cleaning: a meta-analysis and spline-based meta-regression of TNF-α, IL-1β, IL-6, and (hs)CRP - Cardisciani, Martina; Di Nicolantonio, Sara; Altamura, Serena; Ortu, Eleonora; Del Pinto, Rita; Pietropaoli, Davide (Frontiers in Immunology, 2025)
IntroductionChronic periodontitis is linked to systemic inflammation and cardiovascular risk, yet the temporal trajectory and magnitude of systemic cytokine reduction following nonsurgical-periodontal-therapy (NSPT) remain underexplored. We conducted a meta-analysis and spline-based meta-regression to assess whether intensive NSPT, compared to standard therapy, produces sustained reductions in circulating TNF-α, IL-1β, IL-6 and high-sensitivity C-reactive protein (hs-CRP).MethodsWe systematically searched major databases for interventional studies published until January 2024 comparing intensive vs. standard NSPT on inflammatory markers. Using a custom R pipeline, standardized mean differences (SMDs), 95% confidence intervals (Cis) heterogeneity (I²) and stratified analyses by phenotype (e.g., smoking, diabetes) and time were performed. A spline-based mixed-effects meta-regression explored temporal dynamics of inflammatory reduction in the intensive group.ResultsFrom 216 observations (14,374 paired values), intensive NSPT led to significantly greater reductions in TNF-α (SMD –0.59, 95% CI –1.02 to –0.16; P=0.008), IL-6 (SMD –0.20, 95% CI –0.39 to –0.00; P=0.046) and hs-CRP (SMD –1.17, 95% CI –2.18 to –0.16; P=0.024) compared to standard therapy. IL-1β showed a near-significant reduction (SMD –4.14, P=0.052). Standard therapy was paradoxically associated with greater CRP reduction (SMD –0.30, P=0.001). Age, tooth count and year of publication moderated effects. Early benefits emerged within 3 months for TNF-α and 6 months for IL-1β. Although no strong nonlinear time-response was confirmed (QM = 4.23, P=0.2372),a potential rebound in cytokine suppression was suggested. The overall anti-inflammatory effect remained significant.DiscussionIntensive NSPT reduces systemic inflammation particularly in younger, non-smoking individuals. The potential rebound in inflammatory markers underscores the need for longitudinal studies but, supports the systemic immunoregulatory effect of periodontal therapy.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO, identifier CDR42024503063.